1996
DOI: 10.1590/s0103-84781996000200013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of enteropathogenic and enterotoxigenic Escherichia Coli in foods of animal origin in southern Brazil

Abstract: Prevalence of Escherichia coli in foods of animal origin from the city of Pelotas, Brazil, was determined. The ocurrence of enterotoxigenic (ETEC) and classic enteropathogenic (EPEC) serogroups among E. coli isolates was determined. E. coli was isolated from 68% of the food samples surveyed. Of 36 food samples tested, 11(30%) and 24(66%) were positive for EPEC and ETEC strains respectively. However, of 187 E. coli isolates tested, 30(16%) were EPEC compared to 75(40%) which were ETEC. The antibiotic resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…The presence of this pathogen in milk proved to be variable in different regions. In Brazil, Aleixo and Aver [ 64 ] reported EPEC in 25% milk samples while 26 (27.7%) from bulk milk were EPEC in Trinidad [ 65 ]. These values were higher than the 3.09% reported by Holko et al [ 66 ] from Slovakia and that of Altalhi and Hussen [ 41 ], Saudi Arabia.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of this pathogen in milk proved to be variable in different regions. In Brazil, Aleixo and Aver [ 64 ] reported EPEC in 25% milk samples while 26 (27.7%) from bulk milk were EPEC in Trinidad [ 65 ]. These values were higher than the 3.09% reported by Holko et al [ 66 ] from Slovakia and that of Altalhi and Hussen [ 41 ], Saudi Arabia.…”
Section: Resultsmentioning
confidence: 99%
“…We showed that the EPEC prevalence in raw milk samples was 8.25%; however, the presence ofthis pathogene in milk proved to be variable in different regions. In Brazil, Aleixo and Aver (17) reported EPEC in 25% milk samples. In another report, of a total of 175 bulk milk samplesstudied, 83 (47.4%) contained E.coli, and 26 (27.7%) of 94 strains of E.coli isolated from bulkmilk were EPEC (18).…”
Section: Discussionmentioning
confidence: 99%
“…Além da constatação de contaminação fecal, a presença dessa bactéria pode ter um significado particularmente importante, uma vez que existem linhagens enteropatogênicas para o homem e animais (Komacki & Marth, 1982). Alimentos contaminados com E. coli enteropatogênicas são um fator importante na contribuição para a alta incidência de diarréias em países em desenvolvimento (Aleixo & A ver, 1996).…”
Section: Grupo Coliformeunclassified